STRUKTUR SEMANTIK PRONOMINA PERSONA DALAM SISTEM SAPAAN BAHASA BALI - Kamajaya, I Ketut Agus Adi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 21 (2014): March 2014, 2014)
Each item of pronoun has the semantic structure that is constructed by the configuration of meaning that reflects the original characteristic of its culture. The Semantic structure of the pronoun in a language can be very complex and complicated, it is because the influence of its cultural background. A number of personal pronouns in Balinese terms of address that derive several semantic primitives, namely; kai, waké, icang, bena, tiang, titiang, gelah, manira, ulun ‘I’, cai, nyai, ragané, jeroné, gusti, iratu ‘you’, dan ia, dané, ipun, ida ‘someone’, ‘something’/ ‘thing’, ‘people’/’person’, ‘body’. As for describing the semantic structure in each argument of these pronouns, the Natural Semantic Metalanguage Theory (NSM) is applied as a basic reference and also used as an analitical tool, which focuses on the elements of form and meaning.
Keywords: semantic structure, pronoun, term of address